2020
DOI: 10.1177/2332858420932235
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Evaluation and Teacher Turnover in Equilibrium: Evidence From DC Public Schools

Abstract: Teacher turnover is an enduring concern in education policy and can incur substantial costs to students. Policies often address turnover broadly, yet effects turn on net differences in the effectiveness of exiting and entering teachers, in addition to the disruption dealt to classrooms. Recent research has shown mixed effects of teacher evaluation policies, but even where evaluation-induced differential turnover initially benefited students, gains might disappear or reverse as the stock of less effective teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Reducing teacher churn, or the transfer of teachers from one school or profession to another, may help alleviate teacher shortages. However, a study has shown that one in three teachers quit their positions for reasons other than retirement, creating a need for new teachers in the United States around 90 per cent of the year ( James and Wyckoff, 2020 ). To alleviate teacher shortages, educational systems need to address the issues that lead to high turnover.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reducing teacher churn, or the transfer of teachers from one school or profession to another, may help alleviate teacher shortages. However, a study has shown that one in three teachers quit their positions for reasons other than retirement, creating a need for new teachers in the United States around 90 per cent of the year ( James and Wyckoff, 2020 ). To alleviate teacher shortages, educational systems need to address the issues that lead to high turnover.…”
Section: Introductionmentioning
confidence: 99%
“…Many past policies and studies portray teacher retention as clearly helpful ( Carver-Thomas and Darling-Hammond, 2019 ). This position may not be accurate if rigorous and reliable measurements of teacher performance are lacking given the evidence that teacher turnover is harmful to learners ( James and Wyckoff, 2020 ) and damaging to secondary school objectives ( Omorobi et al., 2020 ; Owan et al., 2019 ). However, the compositional impact of teacher turnover is still unknown since it relies on the various impacts of outgoing and incoming instructors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gibbons et al, 2021; Ost & Schiman, 2015). Alternatively, churn could be beneficial if teachers learn from diverse experiences, new teachers replace less effective ones (e.g., James & Wyckoff, 2020), and educators find better matches with schools or roles that ultimately improve their productivity (e.g., Jackson, 2013).…”
mentioning
confidence: 99%
“…Studies that use individual fixed effects to compare performance in all years in which teachers change schools or grades with years that they are stable consistently find negative impacts of churn on student and teacher outcomes (Atteberry et al, 2016; Blazar, 2015; Ost, 2014; Ost & Schiman, 2015). However, studies that use an event study framework to examine a single instance of churn find positive effects for teachers (i.e., Jackson, 2013), as does a study that examines the share of exiting teachers on student achievement and teacher quality (James & Wyckoff, 2020). These varying approaches draw on different reference periods, incorporate different numbers of churn events, and examine churn at different levels (e.g., teacher-level, student-level, school-grade-level), which may complicate our understanding of churn.…”
mentioning
confidence: 99%